PENGARUH MODEL SNOWBALL THROWING TERHADAP HASIL BELAJAR SISWA KELAS V PADA MATA PELAJARAN PKn DI SD INPRES XX SOLOT - Lukas Bera (Equilibrium: Jurnal Penelitian Pendidikan dan Ekonomi, 2020)
ABSTRACTThis study aims to determine student learning outcomes by using the snowball throwing modelon PKn subjects in the diversity of ethnic groups in Indonesia towards the learning outcomes ofstudents in class V SD Inpres XX Solot Nita District, Sikka Regency. This research is aquantitative study with the tipe of experimental research method used in this study using thepre-experimental (nondesings) type one-group pretest-design method. The population andresearch sample were all students of class V which numbered 14 students. The test instrumentused to determine is in the form of a pre-test and post-test. Based on the learning outcomes thevalues obtained the average experimental class in the group that was treated before that is 67,5(pre-test) and the group that has been treated 8,21 (post-test) from the results of hypothesistesting and the basis of taking the value is significant. (2-tailed) is 0,000 while the significancelevel is 0,05. Eating a probability value of 0,05 or 0,000 is smaller than 0,05. This means H isaccepted and H0 is rejected. Thus the influence of the application of the snowball throwingmodel on the PKn learning outcomes in the material of Ethic Diversity in Indonesia is the ClassV Elementary School Student Inpres XX Solot Sikka District. Sikka Regency 2018/2019.Keywords: the application of the snowball throwing model, learning outcomes.